2019
DOI: 10.1182/blood-2018-07-861237
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil α-defensins promote thrombosis in vivo by altering fibrin formation, structure, and stability

Abstract: Inflammation and thrombosis are integrated, mutually reinforcing processes, but the interregulatory mechanisms are incompletely defined. Here, we examined the contribution of α-defensins (α-defs), antimicrobial proteins released from activated human neutrophils, on clot formation in vitro and in vivo. Activation of the intrinsic pathway of coagulation stimulates release of α-defs from neutrophils. α-Defs accelerate fibrin polymerization, increase fiber density and branching, incorporate into nascent fibrin clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 84 publications
4
75
0
1
Order By: Relevance
“…Platelet-driven clot contraction results in compression of RBCs into a tightly packed interior core with an accompanying shape change to polyhedral cells, named polyhedrocytes, whereas fibrin and platelets are mostly on the surface 17 . Polyhedrocytes have also been observed in intracoronary thrombi taken from patients post ST-elevation myocardial infarction 8,17,18 as well as in ex vivo thrombi, venous clots and postmortem pulmonary emboli 12,19,20 . In vitro studies of clot contraction have demonstrated that the kinetics of clot contraction are accelerated and extent of contraction is enhanced by higher platelet levels and inhibited by RBCs and higher fibrinogen concentrations 21 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Platelet-driven clot contraction results in compression of RBCs into a tightly packed interior core with an accompanying shape change to polyhedral cells, named polyhedrocytes, whereas fibrin and platelets are mostly on the surface 17 . Polyhedrocytes have also been observed in intracoronary thrombi taken from patients post ST-elevation myocardial infarction 8,17,18 as well as in ex vivo thrombi, venous clots and postmortem pulmonary emboli 12,19,20 . In vitro studies of clot contraction have demonstrated that the kinetics of clot contraction are accelerated and extent of contraction is enhanced by higher platelet levels and inhibited by RBCs and higher fibrinogen concentrations 21 .…”
mentioning
confidence: 94%
“…It is generally thought that RBCs are trapped in venous clots and might thereby increase vascular occlusion, but that they otherwise contribute little to arterial occlusion. There is now increasing evidence that RBCs play a substantial role in clotting 12 . Sub-fractions of RBCs express phosphatidylserine on their surface and thus support thrombin generation 13,14 .…”
mentioning
confidence: 99%
“…In this issue of Blood, Langerak et al report on the prognostic value of minimal residual disease (MRD) status in elderly patients with comorbid chronic lymphocytic leukemia (CLL) who were treated on the phase 3 CLL11 trial with chlorambucil plus rituximab (R-Chl) or chorambucil plus obinutuzumab (G-Chl). 1 The authors found that high levels of MRD were independently associated with shorter progression-free survival (PFS) and overall survival (OS) and reported that the G-Chl regimen was superior to R-Chl in terms of inducing MRD-negative remissions. 2 On the basis of these findings and the growing pool of data about posttherapy MRD status in CLL patients, the authors suggest that MRD has the potential to become a surrogate marker for survival in clinical trials.…”
Section: Highs and Lows Of Minimal Residual Disease In Cll Deborah Mmentioning
confidence: 99%
“…It is well appreciated that alterations in the fibrin clot profile are directly associated with different clinical pathologies, including conditions associated with bleeding and thrombosis. [7][8][9][10][11][12] Therefore, the development of interventions to modify fibrin clot structure and stability to prevent pathologic hemorrhage and thrombosis in systemic inflammation is an unmet medical need.…”
Section: Introductionmentioning
confidence: 99%